HUBUNGAN PELAYANAN MANAJEMEN AKADEMIK, SARANA PRASARANA, EKSPEKTASI KARIR TERHADAP PRESTASI AKADEMI MAHASISWA JURUSAN KEPERAWATAN GIGI POLITEKNIK KESEHATAN DENPASAR TAHUN AKADEMIK 2O11/I2O2 - I Gusti Ayu Raiyanti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
This study was conducted in order to find out the correlation between academic management service and academic achievement; facilities and infrastructure and academie achievement; career expectation and academic achievement simultaneously towards the academic student student at the department of Dental Health, Polytechnic of Health Denpasar. It was quantitative study, by employing an ex-post facto design. The data were analyzed by using Linear Regression. The population of the study consisted of 64 students at were collected by using questionnaire, and the secondary data were collected by document recording of the student academic scores. The findings indicaed that 1) there was positive and significant correction between academic management service and the student academic achievement with cofficient correlation of (r) 0,784 and the regression equation Y: 2.040+0.007X1 with contribution score of 61,4 % , 2) there was a positive and significant correction between educational infrastructure and student academic achievement with coefficient correlation of (r) 0,493 and the regression equation Y: 1,967+0,008X2 with contributing score 24,3%, 3) there was a positive and significant correction between the career expectation and student academic achievement with cofficient conelation of (r) 0,249 and the regression equation Y: 2,368 +0,007 X3 with contributing scare of 28,5 %, 4) there was simultaneous positive and significant correction between the academic management services, educational facilities and infrastructures, and career academic expectation of and the student academic achievement with coefficient correlation of (r) 0,832 and regression equation Y:1,48+0,002X1+ 0,003X2+0,006X3 with contributing score of 69,2 %. Based on the finding it could be conclused that the academic management service, educational facilities and infrastructures, and career academic expection could affect the academic achievement of the students at the Department of Dental Health, Polytechnic of Health Denpasar.